THE ROLE OF GUIDANCE AND COUNSELING TEACHERS IN THE IMPLEMENTATION OF RESPONSIVE SERVICES IN JUNIOR HIGH SCHOOLS - Syah, Erik Farhan; Ali, Sri Liana (PT Altin Riset Publishing, 2025)
There are guidance and counseling services that can be used by students/counselors in solving their problems. The service that can be used by students when experiencing issues is responsive, a responsive service is a service that is provided to students as soon as possible, so that the process of completing their assignments is not disrupted. Responsive services have several types of implementations used depending on the issues the students are experiencing. These types of services are individual counseling, collaboration with related parties, referrals (case-hand experts), consultation, and case conferences. Responsive services are provided with a purpose to help students/counselors who are experiencing certain problems related to personal, social, learning, and career development.